STATE INTERVENTION IN NIGERIA’S MARITIME SECTOR: CHALLENGES AND POLICY SOLUTIONS - Jande, Jacob Terhemba (African Journal of Social and Behavioural Sciences, 2025)
This study examines the role of the Nigerian state in developing the maritime sector, focusing on the challenges it faces and the way forward. The maritime sector is vital to Nigeria’s economy, contributing to trade, job creation, and revenue. However, it is held back by issues such as poor infrastructure, corruption, ineffective regulations, and insecurity. The researcher used secondary data as a method of data collection, and journal articles, books, and conference papers on the maritime sector were utilised. Qualitative analysis was used to analyse the data collected. The work adopted three theoretical frameworks to analyse the role of the state in the maritime sector. First, the Public Goods Theory, Developmental State Theory, and Human Rights Theory frame the discussion. The findings reveal that while some improvements have been made, key challenges such as insufficient funding, regulatory weaknesses, and security threats persist. In the end, the paper recommends strengthening regulatory frameworks, investing in modern infrastructure, and enhancing security measures. It also calls for more international collaboration and the use of technology to improve efficiency.